From disposable income to residual income: A decomposition of inequality in Austria - Neuhuber, Tatjana; Schneider, Antonia Elisabeth (Wirtschaft und Gesellschaft, 2026)
Income inequality is commonly measured using disposable household income, yet this approach ignores the necessary expenditures households must incur. When costs such as housing, energy, food and transport absorb a substantial share of resources, disposable income may misrepresent effective living standards. This paper analyses income inequality in Austria using a residual income perspective that deducts essential expenditures from equivalized household income. Using representative microdata on 6,873 households, we compare inequality levels based on disposable and residual income, apply a Lerman-Yitzhaki Gini decomposition to identify the contribution of individual expenditure categories, and examine re-ranking within the income distribution using transition matrices and subgroup analyses. We find that inequality is substantially higher when measured on residual income, indicating that conventional measures understate disparities in disposable monetary resources. While disposable income remains the dominant structural determinant of inequality, necessary expenditures exert heterogeneous effects. Housing costs, particularly rent, increase inequality, whereas other necessities exhibit neutral or mildly equalizing effects. Our re-ranking analysis shows a significant reallocation of households in the lower and middle segments of the income distribution, with pronounced regional and household-type differences. These findings highlight the central role of necessary costs in shaping inequality and demonstrate the value of residual income measures for assessing living standards.